"Sprachpraxis" and Mass Customization - Geiselbrechtinger, Conor (Linguistik Online, 2012)
The language component of a degree in English in Germany, or "Sprachpraxis" as it is known in some universities, has in recent years faced a number challenges. Not only are German universities adapting to the B.A./M.A. system but also the very nature of teaching English globally, primarily teaching English as a Lingua Franca (E.L.F.), has had profound effects. This paper aims to explore the most salient questions that have arisen with regard to issues such the role of the native speaker (NS), identity, culture and language. Further, the question will be discussed as to how "mass customization" may be directly applied to the German university. While the introduction of such a system is not without its problems, it could be beneficial to the student, the practitioner and the university as a whole.